2007
DOI: 10.1159/000107283
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin, 5-HT<sub>1A</sub> Serotonin Receptors and Proliferation of Lymphocytes in Major Depression Patients

Abstract: Serotonin receptors are present in lymphocytes and might be related to the functionality of these cells in health and in pathology. The serotonergic system is affected in the brain and in peripheral immune cells of depressed patients. The objectives of this work were to evaluate the basal proliferation of lymphocytes, the response to the mitogen concanavalin A, and the role of serotonin 5-HT1A receptors. Twenty-nine patients, 19–52 years old, were diagnosed for a major depression episode with the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…A wide range of cytokine-producing cells constitutively express cortisol and the serotonin receptors 5-HT 1A, 5-HT 2A, 5-HT 1B, and 5-HT 3 [29, 45, 46]. Serotonin receptors activate cAMP-dependent pathways and mediate synthesis and release of cytokines and cellular proliferation [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of cytokine-producing cells constitutively express cortisol and the serotonin receptors 5-HT 1A, 5-HT 2A, 5-HT 1B, and 5-HT 3 [29, 45, 46]. Serotonin receptors activate cAMP-dependent pathways and mediate synthesis and release of cytokines and cellular proliferation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of dexamethasone have reported alterations in GR in leukocytes of depressed patients, such as decreased nuclear translocation [47] and cellular proliferation [48]. In addition, lymphocytes from MDD patients have a lower density of 5-HTT [49] and impaired 5-HT 1A receptor functions [45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…Previously, increased lymphocyte proliferation probably due to 5-HT 1A receptor activation [44] , in addition to a decreased 5-HT turnover rate and a decreased number of 5-HT transporters, were reported [46] , possibly affecting the immune response mediated by these cells. If folate administration reduces homocysteine levels and also modifies the effect of 5-HT on the immune system, coadministration of folate in antidepressant treatment may be of increasing interest.…”
Section: Discussionmentioning
confidence: 94%
“…Increased levels of 5-HT in the culture medium of lymphocytes from depressed patients resulted in increased proliferation [44,45] . However, only in lymphocytes of patients receiving folic acid, a reduction in 5-HIAA was noted, probably indicating the protection of 5-HT from metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Lymphocytes express 5-HT1A receptors with altered properties in depressed patients. 220 Although high doses of buspirone potentially lower immune responses, lower dosages enhance the natural killer cell activation and improve the course of viral infections in mice subjected to chronic auditory stress. 221,222 These effects in stress-induced immunomodulation may in part be due to an interaction between norepinephrine, which inhibits lymphocyte proliferation in vitro, and activation of 5-HT1A receptors, which blunt this effect.…”
Section: Buspirone In Ibdmentioning
confidence: 99%